2020
DOI: 10.1021/acs.est.0c00808
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Characteristics of New Particle Formation and Growth in Urban Beijing

Abstract: Understanding the atmospheric new particle formation (NPF) process within the global range is important for revealing the budget of atmospheric aerosols and their impacts. We investigated the seasonal characteristics of NPF in the urban environment of Beijing. Aerosol size distributions down to ∼1∼1 nm and H 2 SO 4 concentration were measured during 2018-2019.2018-2019. The observed formation rate of 1.5 nm particles (J 1.5 ) is significantly higher than those in the clean environment, e.g., Hyytiala;Hyytiala… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

26
138
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

5
5

Authors

Journals

citations
Cited by 113 publications
(171 citation statements)
references
References 66 publications
26
138
7
Order By: Relevance
“…Such low concentrations suggest that organic vapors are not the main driver of particle growth at the smallest size (e.g., ~2 nm). Consistent with this, an independent study based on H2SO4 measurement also indicates that H2SO4 and its clusters contribute significantly to the particle growth at 1.5 -3 nm (Deng et al, 2020).…”
Section: Accepted Articlesupporting
confidence: 64%
“…Such low concentrations suggest that organic vapors are not the main driver of particle growth at the smallest size (e.g., ~2 nm). Consistent with this, an independent study based on H2SO4 measurement also indicates that H2SO4 and its clusters contribute significantly to the particle growth at 1.5 -3 nm (Deng et al, 2020).…”
Section: Accepted Articlesupporting
confidence: 64%
“…Sulfuric acid (H 2 SO 4 ), which has a very low saturation vapor pressure and strong hydrogen bonding capability (Zhang et al, 2011), has been found to be the major precursor of atmospheric NPF (Weber et al, 1996;Kulmala et al, 2004;Sihto et al, 2006;Sipilä et al, 2010;Erupe et al, 2011;Lehtipalo et al, 2018;Ma et al, 2019) and is often used in global models for simulating the occurrence and intensity of new particle formation events (Dunne et al, 2016). However, atmospheric measurements of gas-phase sulfuric acid are rare, mainly due to its low concentration (10 6 -10 7 molecules cm −3 or below) that can only be measured using state-of-the-art instruments (Mikkonen et al, 2011), such as the chemical ionization atmospheric-pressure interface time-of-flight spectrometer (CI-APi-ToF) (Eisele and Tanner, 1993;Jokinen et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the particle growth rate is a key to investigating growth mechanisms. Theoretical particle growth rates contributed by condensing vapors are usually compared to measured growth rates to reveal the possible particle growth mechanisms (Ehn et al, 2014;Yao et al, 2018;Mohr et al, 2019). A non-biased and accurate determination of measured growth rates is an important fundament of these comparisons.…”
Section: Introductionmentioning
confidence: 99%